Verbs in the Linguistic Chronological Context (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The research (Verbs in the Linguistic Chronological Context) notes the importance of studying the linguistic temporal dimension and shedding light on the study of linguistic time in verbs in particular, because of its great importance in understanding the contextual connotation, and highlighting the diversity of temporal uses within the Arabic sentence through verbs and their meanings within the context, especially with regard to the actual forms in the Qur'anic verses.It was necessary to talk about the meaning of linguistic time and its relationship with other types of tenses that constitute an overlap with linguistic time, and then moved on to define the multiple temporal meanings within the context of the Arabic verb sentence by talking about time in the three verbal forms: (did, do, do), and to define the meanings from which each verb form emerges, whether abstract or with the presence of tools that precede the verb.This chronological diversity of the uses of the actual Arabic forms is a testament to the depth and vitality of our language derived from the language of the Holy Qur'an. This research has tried to limit the Arabic linguistic time in a clear framework, which has its own clear pillars and rules, and has its multiple contextual variations, taking the Qur'anic verses as an abundant source to highlight this temporal diversity.
Keywords: verbs, context, time, linguistics